Introduction to the research handbook on academic careers and managing academics - Sarrico, Cláudia S. (2022)
This chapter introduces the rationale for looking at how academics are managed, as their status as an elite profession has been questioned. It discusses the multitude of factors at play in managing academics, such as the expansion of higher education, the widespread changes in employment status, the evolving processes to attract and retain talent in the academic profession, the digitalisation and increasing diversity of academic work, the global academic labour market, and the longevity of the academic workforce. It then presents the chapters included in the research handbook on Managing Academics that contribute to a better understanding of how academics are managed at national and institutional levels. A first set of chapters focuses on the changing context for managing academics, a second part discusses the role of academics and other higher education professionals and their relationship, a third group of chapters centres on the theme of gendered academic careers, a fourth collection of chapters delves on the performance of academics, a fifth sequence of chapters looks at human resource management of academics, a sixth section of the handbook analyses mobility and internationalisation of academics, and a final part discusses the theme of age and the generational gaps present in current academia.